Accounting information system and business organizations - Cushing, Barry E. (USA : Addison-Wesley Publishing, 1982)
This book is aimed at helping accountant to effectively interact in the business world with information systems. It provides students and readers with essential elements for preparation of accounting career.
includes index
jbi, 21/03/2018.
loan
Keywords: Accounting; Management information systems; Information storage and retrieval systems